Spatial distribution of dysplasia in Barrett’s esophagus segments before and after endoscopic ablation therapy: a meta-analysis - Garg, Shashank; Xie, Jesse; Inamdar, Sumant; Thomas, Sheila L.; Trindade, Arvind J. (Endoscopy, 2020)
Background Dysplasia in Barrett’s esophagus (BE) is focal and difficult to locate. The aim of this meta-analysis was to understand the spatial distribution of dysplasia in BE before and after endoscopic ablation therapy.Methods A systematic search was performed of multiple databases to July 2019. The location of dysplasia prior to ablation was determined using a clock-face orientation (right or left half of the esophagus). The location of the dysplasia post-ablation was classified as within the tubular esophagus or at the top of the gastric folds (TGF). Results 13 studies with 2234 patients were analyzed. Pooled analysis from six studies (819 lesions in 802 patients) showed that before ablation, dysplasia was more commonly located in the right half versus the left half (odds ratio [OR] 4.3; 95 % confidence interval [CI] 2.33 – 7.93; P < 0.001). Pooled analysis from seven studies showed that dysplasia after ablation recurred in 101 /1432 patients (7.05 %; 95 %CI 5.7 % – 8.4 %). Recurrence of dysplasia was located more commonly at the TGF (n = 68) than in the tubular esophagus (n = 34; OR 5.33; 95 %CI 1.75 – 16.21; P = 0.003). Of the esophageal lesions, 90 % (27 /30) were visible, whereas only 46 % (23 /50) of the recurrent dysplastic lesions at the TGF were visible (P < 0.001). Conclusion Before ablation, dysplasia in BE is found more frequently in the right half of the esophagus versus the left. Post-ablation recurrence is more commonly found in the TGF and is non-visible, compared with the tubular esophagus, which is mainly visible.